The impact of teacher qualifications and experience on student satisfaction: A mediating and moderating research model - Usman Aslam; Muqqadas Rehman; Muhammad Kashif Imran; Farwa Muqadas (Pakistan Journal of Commerce and Social Sciences (PJCSS), 2016)
Every economy has three major sectors: manufacturing, trading and services. The contribution of service sector has become increasingly important for countries' economic wellbeing. The education sector has received greater local and foreign direct investment. This research examines the relationships among teacher qualifications, teacher experience, and student satisfaction. It also investigates whether teacher skills and methods, and knowledge-sharing mediate the association between teacher qualifications, experience, and student satisfaction. Moreover, the moderating effect of a knowledge-intensive culture examines between teaching skills and methods, knowledge-sharing and students satisfaction. The data were collected from 440 teachers/instructors of top ranking and well-known Private Pakistani universities. The results reveal that a teacher qualification is the strongest predictor of student satisfaction than teacher experience. Teacher skills and methods, and effective knowledge-sharing partially mediated the relationship between teachers experience, qualifications and students satisfaction. Finally, knowledge-intensive culture has moderated and strengthened the relationship between teachers' skills and methods, effective knowledge-sharing and student satisfaction. This study provides new avenues for the top managements of education institutions to upgrade education system by involving student that is key stakeholder and best evaluator of teacher performance.
Keywords: 330; teacher qualifications; teacher experience; teacher skills and methods; effective knowledge-sharing; knowledge-intensive culture; student satisfaction